Is it risky to go green? A volatility analysis of the green bond market. (1st October 2016) - Pham, Linh
ABSTRACT: Since its inception in 2007, the green bond market has experienced a compound growth rate of 50% annually. In 2014, green bond issuance totaled USD 36.6 billion, more than threefold its previous year's level of USD 11 billion. This new market is a response to the growing demand of investors for financial investments that are beneficial both environmentally and economically. As the green bond market continues to grow, it is important to obtain a better understanding of the risk and return behavior of the market. This paper is the first to analyze the volatility behavior of the green bond market using data on daily closing prices of the S&P green bond indices between April 2010 and April 2015. Building on a multivariate GARCH framework, my empirical results show that the 'labeled' segment of the green bond market experiences large volatility clustering while the pattern of volatility clustering is weaker in the 'unlabeled' segment of the market. I also found that a shock in the overall conventional bond market tends to spill over into the green bond market, where this spillover effect is variable over time. These results are meaningful insights into this new, yet very promising market, therefore, have important implications for asset pricing, portfolio management and risk management.